Implementation of Enterprise Architecture Zachman Framework at PT. Shopee Internasional Indonesia (Shopee Application) - Annisa Paramaswary Aslam; Widuri Rahayu; Andika Isma (Indonesian Journal of Enterprise Architecture, 2023)
The development of information technology and increasingly fierce competition in business life requires companies to have a strong and efficient information architecture to optimize their business. The framework that can be used to develop information architecture is the Zachman Framework. The purpose of this research is to examine the implementation of the Zachman Framework in the context of developing information architecture at Shopee. The results showed that the Zachman Framework provides a comprehensive framework for the development of Shopee's information architecture. Elements of the Zachman Framework such as perspectives (who, what, when, where, why, how), objects (data, activities, networks, people, time, motivation), and usage can be used to describe and organize various aspects of an enterprise's information architecture. The implementation of the Zachman Framework helps Shopee design, analyze, and design information systems that suit the company's business needs and strategies.